(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Humour andlaughter are the greatestvirtues that God has bestowedon man. A sense of humour makes one see one‟s proper place in this world, and teaches him tosee things in proportion. Both humour and laughter are universal, though there arenational differences on certain aspects. Theyhave their place in all arts andtheir enjoyment leadsto aesthetic experience ofa unique kind.